PENGARUH PENYULUHAN KESEHATAN TERHADAP SIKAP IBU DALAM PEMBERIAN MAKANAN TAMBAHAN PADA BAYI USIA 6-12 BULAN DI RW IV KELURAHAN TAMANGAPA KECAMATAN MANGGALA MAKASSAR - NFN WIRMANDO (Sekolah Tinggi Ilmu Kesehatan Stella Maris Makassar, 2019)
Entering the age of 6 months, children desperately need additional food to meet the nutritional needs of children who are not contained in breast milk. But, due the lack of information from health workers, there are still many mothers who have less good attitude in providing supplementary food to the child. The purpose of this research is to know the influence of health counseling to mother attitude in supplementary feeding for baby 6-12 months in RW IV Kelurahan Tamangapa Kecamatan Manggala Makassar. This type of research was a pre experimental with one group pre-post test design approach. The population of this research was all mothers who have baby aged 6-12 months in RW IV kelurahan Tamangapa Kecamatan Manggala Makassar. Sampling technique was non probability sampling with the accidental sampling approach. Total samples in this research were 38 respondents and data collection was done by using a questionnaire. The statistical test used was the statistical test of Wilcoxon (to know the influence of health counseling to mother's attitude) and obtained value ? = 0,000. Based on the statistical test known value ? < ? (0,05) and can also see the value of Z hit =3,606 and value Z tab =1,65. This shows that Z hit > Z tab. It can be concluded that the null hypothesis (Ho) was rejected and the alternative hypothesis (Ha) were accepted meaning there was influence of health counseling to mother's attitude in supplementary feeding. Therefore, through health counseling and other information media is expected that the mothers want to care and change the attitude of the less good to be better in providing supplementary feeding to their baby.